Recent advances in incretin-based therapy for the treatment of cognitive impairment associated to the type 2 diabetes mellitus: preclinical and clinical studies - a narrative review - Giofrè, Federica; Zaffina, Isabella; Pelle, Maria Chiara; Arturi, Franco (Frontiers in Endocrinology, 2025)
It is well-established that individuals with type 2 diabetes mellitus (T2DM) have an increased risk of developing cognitive impairment and dementia, suggesting a close relation between hyperglycemia, insulin resistance, and chronic inflammation. This decline is characterized by a large variety of symptoms going from mild to major form of cognitive impairment characterized of loss of memory, attention, processing speed, and executive function. Preserving the physiological level of glycemia improves cognitive performance, but untreated or inadequately diabetes therapy facilitates the risk of dementia. Some experimental studies have disclosed that drug for diabetes can have protective outcomes on cognitive impairment. In this context, incretin hormone glucagon-like peptide-1 (GLP-1) can reduce blood glucose, improve glucose transport through cell membranes, and to improve brain insulin resistance modulating neuroinflammation. In fact, GLP-1 acts as a neurotransmitter and neuromodulator activating central GLP-1 receptors located in the neurons determining its neurotropic and neuroprotective role in central nervous system. Preclinical and clinical studies suggest the potential role of dipeptidyl peptidase-4 inhibitors (DPP4-i) as therapy for the treatment and prevention of cognitive impairment and dementia. Similarly, several evidences demonstrated that treatment with glucagon-like peptide-1 receptor agonists (GLP-1 RAs) reduces the risk of cognitive impairment and dementia in T2DM patients by improving learning, memory, attention and executive functions. In addition, preclinical studies suggest a possible neuroprotective effect of GLP-1/GIP dual receptor agonist in animal models. The current narrative review, including studies published from September 1987 to September 2025, summarized the recent improvements regarding to the incretin-based therapy for cognitive impairment associated to the type 2 diabetes mellitus.